Резервы совершенствования систем СДЦ импульсных РЛС с попачечной вобуляцией интервалов зондирования - Леховицкий, Д. И.; Рябуха, В. П.; Жуга, Г. А. (ХНУРЭ, 2008)
The distinctions of the optimal system of interperiod processing (IPP) of Gaussian coherent signals on the background of Gaussian clutters from the standard IPP system of the pulse 10 centimeter-band radar with the sounding intervals bundlewise wobbulation are considered. The potential reserves, expediency and promising directions of IPP systems of such radars perfection are estimated on this basis.
Keywords: попачечная вобуляця; интервал зондирования